The Effects of Digital Transformation, Work Competencies, and Intrinsic Motivation on Employee Job Performance: A Study at the Madiun Regency Civil Registration and Population Administration Office - Revi Mariska; Wahna Widhianingrum; Diana Pramudya Wardhani (Golden Ratio of Mapping Idea and Literature Format, 2026)
Optimizing bureaucratic performance is crucial for improving the quality of public services. This study aims to analyze how digital transformation, job competencies, and intrinsic motivation among employees influence job performance. The study employed a quantitative method using a saturation sampling technique, involving 42 employees at the Madiun Regency Population and Civil Registration Office. The data were collected through a questionnaire and then analyzed using the PLS-SEM method with the assistance of SmartPLS 4 software. The empirical results indicate that digital transformation has a non-significant negative effect on employee performance (β=-0.074,p=0.505). Conversely, work competence (β=0.412,p=0.001) and intrinsic motivation (β=0.514,p=0.000) exert positive and statistically significant effects on performance. The coefficient of determination (R^2=0.690) reveals that these three variables collectively account for 69.0% of the variance in employee performance, while the remaining 31.0% is explained by factors outside this research model. The findings of this study indicate that improvements in job competence and intrinsic motivation are important factors in enhancing employee performance, whereas the implementation of digital transformation at the study site has not yet had a significant impact on employee performance.